Aquasomes: Self-assembled systems for the delivery of bioactive molecules - Narang, Neha (Asian Journal of Pharmaceutics (AJP), 2014)
Nanocarriers increase the therapeutic efficacy of the pharmaceutically active agents as they can regulate their release, improve their stability and prolong circulation time by protecting the drug from phagocytosis and premature degradation.These delivery vehicles have the potential to augment the pharmacodynamic and pharmacokinetic profiles of drug molecules, thereby enhancing the therapeutic efficacy of the pharmaceutical agents. Nanoparticles which are fabricated from ceramics consist of a hydroxyapatite core whose surface is noncovalently modified by oligosaccharide on which bioactive material/drug can be absorbed, are known as â€œaquasomes.â€Â This review involves properties, advantages, preparation methods, evaluation,and applications of aquasomes.